Agama sebagai Benteng untuk Mencegah Kasus Kekerasan Seksual Anak Sejak Dini - Ummah, Ulfa Khoirothul; Kurnia, Heri (Universitas Cokroaminoto Yogyakarta, 2021)
Violence is a part that is closely related to a person's frustration and aggressiveness. The perpetrator vents a sense of emotional resentment towards himself who deliberately injures the other party. In this study using a literature review study or literature review where a study relevant to a particular topic that provides an overview of what is discussed and discussed.religion as a solution. As religion exists it is for mankind's own good, protecting all kinds of human interests, inviting righteousness, and forbidding evil. Among the things that become solutions to prevent cases of sexual violence are First, equipping themselves with a complete understanding of religion. Second, set a good example from parents. Third, equip children with knowledge. Fourth, look for a good environment. With so many cases of sexual harassment and sexual violence juxtaposed in the education process, it is very necessary as a nation to see the problem more complexly.